Lifting Economic Sanctions on Iran : Global Effects and Strategic Responses - Ianchovichina, Elena; Devarajan, Shantayanan; Lakatos, Csilla (World Bank, Washington, DC, 2016)
This paper uses a global general equilibrium simulation model to quantify the effects of lifting economic sanctions on Iran with and without strategic responses. Iran benefits the most, with average per capita welfare gains ranging from close to 3 percent, in the case when Iran's crude oil exports to the European Union recover to half their pre-embargo level, to 6.5 percent, in the best case of complete recovery of oil exports to the European Union, successful domestic reforms that enable a strong supply response, and increased market access for Iranian exports in developed markets. Iran could achieve benefits close to the upper range if Gulf Cooperation Council oil exporters limit their crude oil exports to support the oil price. If they do nothing, however, the price of oil will decline by 13 percent in the case of complete recovery of oil exports to the European Union, leaving net oil importers better off and net oil exporters worse off.